2004
DOI: 10.1002/ijc.11641
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygote deficiency in thymidylate synthase enhancer region polymorphism genotype distribution in Hungarian colorectal cancer patients

Abstract: Thymidylate synthase (TS) gene polymorphisms are important as prognostic factors in cancer chemotherapy, but recent results describe that the TS enhancer region (TSER) polymorphic genotypes may also modulate risk for malignancies. Two functionally important and ethnically diverse polymorphisms are present on the TS transcript, TSER, a repeat polymorphism (2 or 3 repeats; 2R, 3R) affecting TS expression, and a 6 bp ins/del polymorphism on the 3 UTR (position TS1494, del6 or ins6), which may influence mRNA stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 21 publications
(25 reference statements)
2
17
1
Order By: Relevance
“…A study conducted by Krajinovic et al showed that genotyping of TS might make it possible to individualize treatment for patients with acute lymphoblastic leukaemia [35]. A case-control study conducted by Adleff et al showed that increased presence of one genotype combination (3R/3R and ins6/del6) in the patient group suggested a possible TS haplotype effect influencing colorectal cancer risk [36]. This supports the results achieved by us.…”
Section: Discussionsupporting
confidence: 83%
“…A study conducted by Krajinovic et al showed that genotyping of TS might make it possible to individualize treatment for patients with acute lymphoblastic leukaemia [35]. A case-control study conducted by Adleff et al showed that increased presence of one genotype combination (3R/3R and ins6/del6) in the patient group suggested a possible TS haplotype effect influencing colorectal cancer risk [36]. This supports the results achieved by us.…”
Section: Discussionsupporting
confidence: 83%
“…This decreased risk was more pronounced among older never smokers, which is not consistent with data on other cancers published previously (15,18,21). Our data suggest that the TS3ЈUTR polymorphism plays an important role in the etiology of SCCHN.…”
Section: Discussioncontrasting
confidence: 83%
“…After reviewing each original paper and extracting data, eight studies were excluded including two studies for overlapping data and six studies for studies on colorectal adenoma (Ulrich et al, 2002;Chen et al, 2004;Goode et al, 2004;Hubner et al, 2006;Hubner et al, 2007;van den Donk et al, 2007). Finally, seven case-control studies with a total of 2723 cases and 4030 controls were included into this meta-analysis (Chen et al, 2003;Adleff et al, 2004;Matsuo et al, 2005;Ulrich et al, 2005;Chen et al, 2006;Carmona et al, 2008;Karpinski et al, 2010). The detailed characteristics of these studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%